Pathogenic Mechanisms and Clinical Correlations in Autoimmune Myasthenic Syndromes - Cetin, Hakan; Vincent, Angela (Seminars in Neurology, 2018)
Autoimmune myasthenic syndromes are antibody-mediated disorders of the neuromuscular junction. Common antigenic targets are the acetylcholine receptor or muscle specific kinase (MuSK) in myasthenia gravis (MG) and the voltage-gated calcium channel in Lambert-Eaton myasthenic syndrome. There is evidence that antibodies directed against other antigens such as low-density lipoprotein receptor-related protein 4 (LRP4) are also involved in MG. The mechanisms by which various antibodies exert their pathogenic effect depend on the IgG subclass and also the epitope location on the antigens. These mechanisms are partly heterogeneous and include antigen degradation, complement activation, direct functional blocking, or disruption of protein–protein interactions. The neuromuscular junction is characterized by a structural and functional plasticity that is able to compensate for some of the neuromuscular junction defects. Here, we discuss the underlying pathogenic mechanisms of the different autoantibodies and correlate them with phenotypic features. The understanding of these elements should help guide the clinical management of patients with autoimmune myasthenic syndromes.
Keywords: neuromuscular junction; acetylcholine receptor; myasthenia gravis; Lambert-Eaton myasthenic syndrome